Hubungan Malaria Pada Ibu Hamil Terhadap Kejadian Berat Badan Lahir Rendah (BBLR) - Sulistyowati, Anisa Nanang; Wardhani, Yeni; Al Adawiyah, Rabiyah (Indonesian Health Issue, 2025)
Background: Malaria is an infectious disease caused by parasites of the plasmodium type which is transmitted through the bite of a female Anopheles mosquito. Malaria infection during pregnancy carries a high risk to the mother, fetus and newborn, resulting in abnormalities in the newborn, namely LBW. The purpose of this study was to determine the effect of malaria incidence on the birth rate of low birth weight (LBW) in the Timika Health Center work area in 2024. This research method uses a quantitative research approach with a cross-sectional design taking data from a medical record in the form of a history of malaria in mothers giving birth in 2024 at the Timika Health Center. The results of this study showed that the majority of respondents with the highest education were high school (59.1%), the age group was 26-30 years (34.1%), respondents with a history of LBW (75%) and the incidence of malaria in mothers (90.1). There is a significant relationship between a history of LBW and the incidence of malaria in mothers at the Timika Health Center in 2024 with a p value of 0.000. Conclusion The prevalence of malaria in pregnant women in the Timika Health Center work area in 2023 was 40 cases, the prevalence of LBW was 33 cases and there was a relationship between the incidence of malaria in mothers and a history of LBW in the Timika Health Center work area in 2024